AKTUALISASI HAMEMAYU HAYUNING BAWONO PADA RUANG PEDESTRIAN MALIOBORO: PERSPEKTIF FENOMENOLOGI DAN KEBERLANJUTAN KOTA (Jurnal Arsitektur ARCADE, 2026)
The Malioboro Corridor is part of the Yogyakarta Philosophical Axis and embodies the philosophy of Hamemayu Hayuning Bawono, which emphasizes harmonious relationships among humans, nature, and God. The transformation of Malioboro into a pedestrian-friendly and low-emission corridor has reshaped pedestrians' spatial experiences while creating opportunities to actualize these philosophical values within the context of contemporary urban development. This study aims to examine pedestrians' spatial experiences and analyze the actualization of Hamemayu Hayuning Bawono in the Malioboro pedestrian corridor from phenomenological and urban sustainability perspectives. A qualitative approach employing Husserlian phenomenology was adopted. Data were collected through field observations, in-depth interviews, and documentation, and analyzed using open coding, axial coding, and selective coding. The findings reveal that pedestrians' spatial experiences foster a strong sense of place, place attachment, and place identity as integral components of the Yogyakarta Philosophical Axis. Furthermore, the philosophy of Hamemayu Hayuning Bawono is actualized through harmonious relationships among humans, nature, and God. The pedestrianization policy and the development of a low-emission corridor demonstrate the implementation of the memayu hayuning bawana principle in promoting a more human-centered and sustainable urban environment.
Keywords: Hamemayu Hayuning Bawono; phenomenology; urban sustainability